Valosin-containing protein (VCP/p97) inhibition reduces viral clearance and induces toxicity associated with muscular damage - Marta del Rio Oliva; Michael Basler (Cell Death and Disease, 2022)
Abstract Valosin-containing protein (VCP)/p97 has emerged as a central regulator of the ubiquitin–proteasome system by connecting ubiquitylation and degradation. The development of CB-5083, an ATPase D2-domain-selective and orally bioavailable inhibitor of VCP/p97, allows targeting of the ubiquitin–proteasome system in human diseases. In this study, we evaluated the effect of CB-5083 on the immune response in mice by using the lymphocytic choriomeningitis virus (LCMV) as an infection model. We demonstrate that LCMV infection increased the susceptibility to CB-5083 treatment in a CD8-independent manner. Administration of CB-5083 to mice reduced the cytotoxic T cell response and impaired viral clearance. Compared to uninfected cells, CB-5083 treatment enhanced the unfolded protein response in LCMV-infected cells. Administration of CB-5083 during the expansion of CD8+ T cells led to strong toxicity in mice within hours, which resulted in enhanced IL-6 levels in the serum and accumulation of poly-ubiquitinated proteins. Furthermore, we linked the observed toxicity to the specific formation of aggregates in the skeletal muscle tissue and the upregulation of both lactate dehydrogenase and creatine kinase in the serum.